2014
DOI: 10.1016/j.bbrc.2014.10.140
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and vasoactive hormone profiles from endothelial cells derived from stem cells of different sources

Abstract: Endothelial cells form a highly specialised lining of all blood vessels where they provide an anti-thrombotic surface on the luminal side and protect the underlying vascular smooth muscle on the abluminal side. Specialised functions of endothelial cells include their unique ability to release vasoactive hormones and to morphologically adapt to complex shear stress. Stem cell derived-endothelial cells have a growing number of applications and will be critical in any organ regeneration programme. Generally endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…As shown previously (19,20), endothelial cells grown out from human blood (BOECs) of healthy volunteers had typical endothelial cell morphology and expressed VEcadherin ( Fig. 1 and Table 1).…”
Section: Resultssupporting
confidence: 85%
“…As shown previously (19,20), endothelial cells grown out from human blood (BOECs) of healthy volunteers had typical endothelial cell morphology and expressed VEcadherin ( Fig. 1 and Table 1).…”
Section: Resultssupporting
confidence: 85%
“…22 Indeed, the release of high levels of ET-1 is a unique defining feature of endothelial cells. 22 Indeed, the release of high levels of ET-1 is a unique defining feature of endothelial cells.…”
Section: Smcs and Pbmcs In Mono-and Coculture Conditionsmentioning
confidence: 99%
“…In culture, endothelial cells from all origins, including BOECs, release high levels (relative to other cell types) of ET-1. 22 Indeed, the release of high levels of ET-1 is a unique defining feature of endothelial cells. As expected, therefore, the BOECs used in our coculture model (Figure 2A) released high levels of ET-1 ( Figure 2B).…”
Section: Smcs and Pbmcs In Mono-and Coculture Conditionsmentioning
confidence: 99%
“…A number of studies have demonstrated the differentiation of hPSCs into ECs [13][14][15][16][17][18][19][20][21][22][23][24]. Several different differentiation approaches have been utilized, all novel in their methodology but with a similar end goal: acquiring functional ECs.…”
Section: Pluripotent Stem Cell Derived Endothelial Cellsmentioning
confidence: 99%